CD36‐dependent signaling mediates fatty acid‐induced gut release of secretin and cholecystokinin. Issue 3 (11th December 2012) - Sundaresan, Sinju; Shahid, Rafiq; Riehl, Terrence E.; Chandra, Rashmi; Nassir, Fatiha; Stenson, William F.; Liddle, Rodger A.; Abumrad, Nada A.
Abstract : Genetic variants in the fatty acid (FA) translocase FAT/CD36 associate with abnormal postprandial lipids and influence risk for the metabolic syndrome. CD36 is abundant on apical enterocyte membranes in the proximal small intestine, where it facilitates FA uptake and FA‐initiated signaling. We explored whether CD36 signaling influences FA‐mediated secretion of cholecystokinin (CCK) and secretin, peptides released by enteroendocrine cells (EECs) in the duodenum/jejunum, which regulate events important for fat digestion and homeostasis. CD36 was immunodetected on apical membranes of secretin‐ and CCK‐positive EECs and colocalized with cytosolic granules. Intragastric lipid administration to CD36 –/– mice released less secretin (–60%) and CCK (–50%) compared with wild‐type mice. Likewise, diminished secretin and CCK responses to FA were observed with CD36 –/– intestinal segments in vitro, arguing against influence of alterations in fat absorption. Signaling mechanisms underlying peptide release were examined in STC‐1 cells stably expressing human CD36 or a signaling‐impaired mutant (CD36K/A). FA stimulation of cells expressing CD36 ( vs. vector or CD36K/A) released more secretin (3.5‐ to 4‐fold) and CCK (2‐ to 3‐fold), generated more cAMP (2‐ to 2.5‐fold), and enhanced protein kinase A activation. Protein kinase A inhibition (H‐89) blunted secretin (80%) but not CCK release, which was reduced (50%) by blocking of calmodulin kinase II (KN‐62). Coculture of STC‐1 cells with Caco‐2 cells stably expressing CD36 did not alter secretin or CCK release, consistent with a minimal effect of adjacent enterocytes. In summary, CD36 is a major mediator of FA‐induced release of CCK and secretin. These peptides contribute to the role of CD36 in fat absorption and to its pleiotropic metabolic effects.—Sundaresan, S., Shahid, R., Riehl, T. E., Chandra, R., Nassir, F., Stenson, W. F., Liddle, R. A., Abumrad, N. A. CD36‐dependent signaling mediates fatty acid‐induced gut release of secretin and cholecystokinin. FASEB J. 27, 1191–1202 (2013). www.fasebj.org